The Influence of Emotional Intelligence and Competence on Employee Performance Mediated by Job Satisfaction - Tutik Lestari; Sarsono Sarsono; Supawi Pawenang (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2024)
The institution must enhance and cultivate staff performance to ensure that the institution's success is intrinsically tied to quality. The objective of this study is to examine the impact of emotional intelligence and competence on employee performance, while considering job satisfaction as a mediating factor, inside the Department of Trade of Surakarta City. This study employs a quantitative method, making use of both primary and secondary data. The study encompasses a total of 73 individuals employed at the Department of Trade of Surakarta. The sampling method employed is saturated sampling, which involves including all members of the population as samples. The study findings indicate that the T-statistic value of 3.444 demonstrates a positive and substantial impact of emotional intelligence on employee performance. Similarly, the T-statistic value of 2.213 indicates a positive and significant influence of competence on employee performance. Furthermore, the T-statistic value of 2.563 indicates that there is a statistically significant and positive relationship between job satisfaction and employee performance. The results indicate that the T-statistic value of 6.293 demonstrates a positive and substantial impact of emotional intelligence on job satisfaction. Similarly, the T-statistic value of 4.850 indicates a positive and significant influence of competence on job satisfaction. This study demonstrates that the T-statistic value of 2.337 indicates a positive and significant impact of emotional intelligence on employee performance through job satisfaction. Similarly, the T-statistic value of 2.254 indicates a positive and significant impact of competence on employee performance through job satisfaction. The study emphasizes the need of cultivating emotional intelligence and enhancing employee competence to enhance their performance.Keywords: Performance, emotional intelligence, competence, job satisfaction.